The functions of angels in Sufi literature - Gallorini, Louise (Islamic history and civilization, 2025)
"This book is a literary study tracing the roles and functions of angels as characters in Sufi literature, based on their functions outlined in the Quran. If you pick up any book discussing Islam or islamic theology, you will probably find angels in it - one never thinks much about them, and they often seem marginal. However, whether real or a simple literary device, what are the angels' real functions in a text? This study proposes to outline their functions, and more specifically what classical Sufi literature (7th--12th century CE) makes of them"-- Provided by publisher